Long-term effects of cyclic therapy with iloprost in systemic sclerosis - A. Grottolo; A. Frigè; E. Danieli; M. Rossi; M. Scarsi; A. Zambruni; P. Airò (PAGEPress Publications, 2011)
Objective: To assess the long-term effects of cyclic infusion of iloprost, a derivative of prostacyclin, on Raynaud's phenomenon- related symptoms and ischemic ulcers in patients with Systemic Sclerosis (SSc). Methods: A retrospective analysis of prospectively collected parameters in 59 consecutive SSc patients, followed at one institution, who were treated for a median time of 52 months with iloprost for severe Raynaud's phenomenon and ischemic ulcers. Results: Among the 50 patients with ischemic ulcers at the start of therapy, 35 (70%) did not show lesions at the last observation. Despite therapy, four patients underwent amputations (two of forefoot, two of finger distal phalanges). Compared to the pre-treatment point, we observed: decrease of the Raynaud's phenomenon VAS (p<0.001), and, in patients with diffuse cutaneous involvement, of the modified Rodnan skin thickness score (p=0.002). The Health Assessment Questionnaire was not significantly improved. Conclusion: Treatment with cyclic iloprost can control Raynaud's phenomenon-related symptoms and ischemic ulcers in the large majority of patients with SSc. However, a disease-modifying effect of this therapy could not be demonstrated.